Major sports events and the transmission of SARS-CoV-2: analysis of seven case-studies in Europe - Signorelli, C.; Odone, A.; Riccò, M.; Bellini, L.; Croci, R.; Oradini-Alacreu, A.; Fiacchini, D.; Burioni, R. (Acta bio-medica: Atenei Parmensis, 2020)
During February and March 2020 some sports events may have played a role in the spread of the Coronavirus disease 2019 (COVID-19) epidemic in Europe (2-4), before health and political authorities decided to suspend them. We have considered seven major sports events scheduled before the onset of COVID-19 epidemic outbreak in Europe: the soccer Champions League matches Atalanta-Valencia (19th February and 11th March), Atlético de Madrid-Liverpool (18th February and 11th March) and Lyon-Juventus (26th February), the "Final-eight" of the Italian Basketball Cup in Pesaro (13 matches from 13th through 16th February with a total of 32,000 attendees) and the Biathlon World Championships in South Tyrol (from 12th through 23rd February, with 165,000 overall attendees). The health indicator we have assessed is the increase in SARS-CoV-2 infection notifications between the 14th and the 21stday after the event (5), considering the mean incubation period, the timing of test execution and the notification of results (7-10).